The Missing Links - Uganda's Economic Reforms and Pro-Poor Growth - Robert Kappel; Jann Lay; Susan Steiner (Deutsche Gesellschaft für Technische Zusammenarbeit (GTZ), 2004)
This article illustrates changing growth regimes in Uganda from pro-poor growth in the 1990s to growth without poverty reduction, actually even a slight increase in poverty, after 2000. Not surprisingly, we find that good agricultural performance is the key determinant of direct pro-poor growth in the 1990s as well as lower agricultural growth is the root cause of the recent increase in poverty. Yet after 2000, low agricultural growth appears to have induced important employment shifts out of agriculture, which have dampened the increase in poverty. We also assess the indirect way of pro-poor growth by analysing the incidence of public spending and the tax system and find that indirect pro-poor growth has only been achieved to a limited extend.
Conference: International Conference on African Development and Poverty Reduction: The Macro-Micro Linkage, 13-15 October 2004, Lord Charles Hotel South Africa
Keywords: 330; Wirtschaftspolitik; Wirtschaftsreform; Wirtschaftswachstum; Armut; Armutspolitik; Uganda